Opportunities for Improving Urban Service Delivery in South Sudan - A Tale of Two Cities : Part 3. Synthesis Report - World Bank (World Bank, Washington, DC, 2018)
This study "Opportunities for Improving Urban Service Delivery in South Sudan: A Tale of Two Cities" comprises a 3 part series. Part I—Service Delivery Status Report—gives a general overview of the service delivery models currently operating the country. Part II—International Case Studies analyzes alternative service delivery models from other countries that are relevant to South Sudan. Part III—Synthesis Report—builds on the first two and investigates models of alternative service delivery in the context of urban South Sudan. Millions of people in the world's newest country, in both urban and rural areas, depend on services delivered wholly or partly by nongovernment entities in this highly fragile, fluid, and often insecure environment that has been mired in conflict and economic challenges since gaining its independence six years ago. The objective of this research is to: identify and analyze successful models of service delivery in select urban areas of South Sudan that can be supported and replicated; recommend relevant international examples of service delivery models that are appropriate to the South Sudanese context; and identify the appropriate role of government in these alternative delivery models . Across the various models identified, this study examines the cost and quality of services provided; access to these services; and the accountability relationships involved in these models.